Effectiveness and safety of ustekinumab maintenance therapy in 103 patients with ulcerative colitis: a GETAID cohort study. Issue 7 (23rd July 2021) - Fumery, Mathurin; Filippi, Jérôme; Abitbol, Vered; Biron, Amélie; Laharie, David; Serrero, Melanie; Altwegg, Romain; Bouhnik, Yoram; Peyrin‐Biroulet, Laurent; Gilletta, Cyrielle; Roblin, Xavier; Pineton de Chambrun, Guillaume; et al.
Summary: Background: Phase III trials have demonstrated the efficacy and safety of ustekinumab in ulcerative colitis (UC), but few real‐life long‐term data are currently available. Aims: To assess the real‐world effectiveness and safety of ustekinumab in patients with UC. Methods: From January to September 2019, all consecutive patients with active UC treated with ustekinumab in a GETAID centre were included. Patients were evaluated at week 52. Remission was defined as a partial Mayo Clinic score ≤2. Results: We included 103 patients with UC (62 men; mean age: 41.2 ± 16.2 years; 52% pancolitis E3) with an insufficient response to immunosuppressants, anti‐TNFs and/or vedolizumab. At week 52, 45 (44%) patients had discontinued ustekinumab mainly due to lack of effectiveness (n = 41). The cumulative probabilities of ustekinumab persistence were 96.1%, 81.6%, 71.7% and 58.4% after 3, 6, 9 and 12 months respectively. The overall steroid‐free clinical remission rate at week 52 was 32% of whom 71% had subscores of null for rectal bleeding and stool frequency. Ten patients underwent colectomy within a median of 6.7 [4.3‐10.6] months. Adverse effects were observed in 15 (16.9%) patients; 4 (4.5%) were severe, including one patient who died from a myocardial infarction. Conclusion: After 52 weeks, over one‐half of patients with refractory UC were still treated by ustekinumab and one‐third were in steroid‐free clinical remission. Abstract : Among 103 patients with ulcerative colitis treated with ustekinumab, one‐third achieved steroid‐free clinical remission and less than 10% were referred to surgery, after a 1‐year follow‐up period. https://doi.org/10.1111/apt.16544